Bibliometric Mapping of Trends in EFL Vocabulary Studies: Performance and Intellectual Structure - Putria Hanindra Sekar Asmarani; Zuliati Rohmah; Siti Maftuhah Damio (FKIP Universitas Lampung, 2026)
Bibliometric analysis of vocabulary in EFL is limited. This limitation is due to the topic's specificity. Updated bibliographic data on vocabulary in EFL is essential to support future research on the topic, specifically in the context of EFL. This study addressed this gap by conducting a bibliometric analysis of 117 research or review articles sourced from the Scopus database. The data were retrieved using the PRISMA data collection scheme, which was later processed and visualized using Biblioshiny-R and VOSViewer. The analysis focused on trends in annual production (2014-2024), key authors, frequently used keywords, and highly cited documents. The results showed that the annual scientific production from 2014-2024 experienced notable fluctuations, with 2014 being the most productive year (31 documents) and 2017 the least (2 documents). The authorship analysis revealed a relatively small group of recurring contributors, such as Qun Wu, Hifen Lin, and Mark Feng Teng, indicating that although productivity per author was modest, these researchers collectively shaped the direction of EFL vocabulary scholarship. Keyword co-occurrence analysis highlighted “vocabulary,” “vocabulary learning,” and “EFL” as the most dominant terms, showing that research in this field focuses strongly on lexical development within foreign-language contexts. Citation analysis showed that Blasco (2015), Klimova (2021), and Sidek (2015) produced the most influential records centered on cognitive linguistics, mobile learning, and vocabulary relationships. This study updates and systematizes the fragmented landscape of EFL vocabulary research, revealing a clear shift toward technology-mediated, corpus-informed, and cognitively oriented approaches. The findings offer a renewed foundation for future researchers to further develop and expand this field. Keywords: bibliometric analysis, EFL, vocabulary.